Efeito de aplicativo móvel na identificação de intercorrências na amamentação e autoeficácia para amamentar: ensaio clínico randomizado - PENHA, Jaiza Sousa (2022)
Introduction: The promotion of breastfeeding can be carried out through the use of educational technologies, which relate theory and practice in the context of teaching and learning of individuals, and have often been assisted by cell phones. Mobile health has several mechanisms, including application software, such as SOS Mama, built with the aim of helping postpartum women in the management of breastfeeding. As hypotheses, we have: puerperal women who accessed the SOS Mama application will identify the presence of breast complications; and will have greater self-efficacy to breastfeed. Objective: To evaluate the effect of the SOS Mama mobile application on the identification of breastfeeding complications and on breastfeeding self-efficacy. Methods: Randomized Clinical Trial developed in the maternity ward of a university hospital in the capital of northeastern Brazil, between September 2021 and January 2022. Postpartum women admitted to rooming-in, accompanied by their baby, over 18 years of age, literate, who had a smartphone and expressed an interest in breastfeeding. The intervention used was the SOS Mama mobile application, developed with the aim of helping lactating women to care for their breasts in the face of breastfeeding difficulties. Participants were allocated into Intervention Group (IG) and Comparison Group (CG). The intervention took place through the presentation, demonstration and recommendations for the use of the SOS Mama for postpartum women in the GI, in the first week after delivery. Data collection took place in three moments: first week postpartum, 15 and 30 days postpartum, with sociodemographic, obstetric and breastfeeding information. Breastfeeding self-efficacy was verified using the Breastfeeding Self-Efficacy Scale. The sample was calculated using the G*Power 3.1 software with a significance level of 5%, resulting in 264 participants. Block randomization was performed. Statistical analyzes were performed at 5% significance in the IBM SPSS program. The study was submitted for ethical consideration, via Plataforma Brasil, approved under opinion No. 4,900,065, and registered in the Brazilian Registry of Clinical Trials with identification RBR-5hm95CW. Results: 270 postpartum women were randomized, 132 in the IG and 138 in the CG. For the identification of breast complications, there was a statistical difference between the groups at 15 days, not being maintained in the 30-day follow up. The puerperal women in the GI were 2.84 times more likely to identify breast complications 15 days after delivery and 1.87 times more likely at 30 days, compared to the comparison group. No puerperal woman showed low self-efficacy to breastfeed. Between the first week and 15 days postpartum, there was an increase in the number of participants with high self-efficacy to breastfeed in both groups. Between 15 and 30 days, the percentage of postpartum women with high self-efficacy remained in the GI (98.5%). In the categorical analysis for high self-efficacy, there was no difference between the groups, but within each group there was statistical significance, regardless of the intervention. Conclusion: SOS Mama was effective in helping postpartum women to identify breast complications related to breastfeeding 15 days after delivery and did not influence the self-efficacy to breastfeed of the postpartum women in the study.